Scaling Workshop Report: Bundled solutions with seed systems, index insurance and climate information to manage agricultural risks (BICSA) - International Water Management Institute; CGIAR Research Program on Climate Change, Agriculture and Food Security; CGIAR Research Program on Water, Land and Ecosystems (2021)
Adaptation to climate change is a vital response to enhance the resilience of these smallholder agricultural livelihoods, more so because of their adverse effect on the food security of the nation. Lack of education and technical skills, poverty, and risks inherent to agricultural investments as well as little access to financial capital are the main reasons for low investments in adaptive capacity enhancements. In response to this long felt need, the International Water Management Institute (IWMI) and national partners in agribusiness, with support from the CGIAR Research Programs on Climate Change, Agriculture and Food Security (CCAFS), and Water, Land and Ecosystems (WLE) organized a scaling agricultural insurance workshop to discuss and further strengthen bundled insurance solutions. Seed, insurance and agrochemical companies in the private sector, as well as weather service providers, participated in the workshop which aimed to promote better resilience among marginal farmers through innovative risk transfer solutions using advanced satellite technology, crop models and IoT tools. The holistic approach to managing floods and drought allows the development of comprehensive risk mitigation plans and rapidly disseminates information that enables water resources and disaster managers, communities and farmers to better manage risks related to climate variability and their impact on agriculture and food security. Present workshop report highlights the key takeaways of the workshop held on 19th May 2021. This workshop was organised with the vision of strengthening the initiative of bundling agricultural insurance and seek to establish strong cooperation among different stakeholders that include the government, private sector, nongovernmental organizations and academic institutions. Key policy makers, implementers, private sector entities (seed companies and the insurance industry) and development partners involved in bundling solutions were among the participants.